The Origin and Evolution of Bills of Exchange Before 1939 - Biadacz , Renata (Studia Oeconomica Posnaniensia, 2016)
The subject of discussion in this article is the genesis of bills of exchange and their circulation since inception in the mid-twelfth century to the 1930s. The aim of the article is to discuss the reasons of establishment of and changes of importance in bills of exchange, outline the development of legal regulations for these bills, and present an accounting of bills of exchange in the interwar period. The first part of the study presents the historical creation of bill of exchange and its development up until the 1930s. The second part exposes key events in the development of laws regarding bills of exchange. The considerations presented in part three highlight problems in the classification of bills and their records in Poland in the second half of nineteenth century and the first 30-year period of the twentieth century. The applied testing method is literature studies based on selected textbooks and scientific papers published in Poland in the late nineteenth and early twentieth century. The article has cognitive qualities because it contains a synthetic overview of the state of knowledge of bills of exchange trade and its accounting in the nineteenth century, which is referred to as a critical period in the development of trade, industry, technique and technology, and thus the development of accounting, also in Poland.